The effectiveness of educational program based on the cooperative learning strategy to development some of mathematical concepts in kindergarten. - علي مرفت (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The aim of the research is to measure the effectiveness of cooperative learning strategy to development of some of mathematical concepts in kindergarten compared to the usual way, To achieve this aim of the research educational program based on the cooperative learning strategy was designed, which included the educational units(third and fourth) of the kindergarten book. In order to measure the effectiveness of the cooperative learning strategy, (15)paragraph visual test mathematical concepts was prepared by the researcher. The study sample consisted of two groups, one experimental (learned by the cooperative learning strategy) and the other one (learned by the usual method) each group included (15) child and a girl. Following the completion of the experiment and the collection of data on pre-post-test, the results were analyzed and analyzed statistically, and showed the following. 1- A statistically significant difference between the mean scores of the children of the experimental and control groups in the test of mathematical concepts in favor of the experimental group. 2- A statistically significant difference between the average scores of children in the experimental group in the testing of mathematical concepts in favor of the post application. 3- There is a statistically significant difference between the average scores of male and female children in the experimental group to test sports concepts for females. The research included a number of proposals, the most important of which was the recruitment work on the cooperative learning strategy as an educational-learning strategy in kindergartens in order to provide the child with many different skills, experiences and concepts, especially mathematical concepts.